Antivirals against animal viruses - Villa, T.G. (Biochem Pharmacol, 2017)
Antivirals are compounds used since the 1960s that can interfere with viral development. Some of these antivirals can be isolated from a variety of sources, such as animals, plants, bacteria or fungi, while others must be obtained by chemical synthesis, either designed or random. Antivirals display a variety of mechanisms of action, and while some of them enhance the animal immune system, others block a specific enzyme or a particular step in the viral replication cycle. As viruses are mandatory intracellular parasites that use the host’s cellular machinery to survive and multiply, it is essential that antivirals do not harm the host. In addition, viruses are continually developing new antiviral resistant strains, due to their high mutation rate, which makes it mandatory to continually search for, or develop, new antiviral compounds. This review describes natural and synthetic antivirals in chronological order, with an emphasis on natural compounds, even when their mechanisms of action are not completely understood, that could serve as the basis for future development of novel and/or complementary antiviral treatments.